156k views
8 votes
4(k+1)=k+10,then 3k=

A. 3/2
B.5/2
C. 2
D. 6​

2 Answers

10 votes

Answer:

it B becuase of the step

Explanation:

step bye step of PEMDAS

User John Wickerson
by
5.3k points
5 votes

Solution:

Note that:

  • Given equation: 4(k + 1) = k + 10
  • To find: 3k

Simplifying the LHS:

  • 4(k + 1) = k + 10
  • => (4 x k) + (4 x 1) = k + 10
  • => 4k + 4 = k + 10

Subtracting k and 4 both sides:

  • 4k + 4 - k - 4 = k + 10 - k - 4
  • => 3k = 6 (No further solution required)

The value of 3k is 6.

User EngineerSpock
by
5.7k points